1989
DOI: 10.1159/000118550
|View full text |Cite
|
Sign up to set email alerts
|

Pattern-Reversal Visual Evoked Potentials in Normal 7- to 15-Year-Old Twins: A Correlation Analysis

Abstract: Pattern-reversal visual evoked potentials (PRVEPs) were tested in 11 sets of monozygotic (MZ) twins and 22 sets of dizygotic (DZ) twins matched on age, sex and educational level. They ranged in age from 7 to 15 years. The PRVEPs of MZ twins exhibited a signifícantly greater degree of similarity than those of DZ twins. The peak latencies and amplitudes of PRVEP components obtained from MZ twin pairs were significantly correlated. The correlation coefficients for the peak latencies of the P2 (or P100) component … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

1990
1990
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
(15 reference statements)
0
2
1
Order By: Relevance
“…3,4 Ristanovic et al reported no significant difference between P-RVEPs of children with common and complicated migraine. 19 Although there were no mean significant P-RVEP abnormalities found in our study, 7 of the 23 patients with MWOA (30%) had latencies exceeding the upper limit of normal. Interestingly, the mean duration of the disease was significantly longer in this subgroup than the other 16 patients with MWOA.…”
Section: Commentscontrasting
confidence: 65%
“…3,4 Ristanovic et al reported no significant difference between P-RVEPs of children with common and complicated migraine. 19 Although there were no mean significant P-RVEP abnormalities found in our study, 7 of the 23 patients with MWOA (30%) had latencies exceeding the upper limit of normal. Interestingly, the mean duration of the disease was significantly longer in this subgroup than the other 16 patients with MWOA.…”
Section: Commentscontrasting
confidence: 65%
“…[6][7][8][9][10] An increased amplitude of both flash and pattern-reversal VEPs (PR-VEPs) was found in juvenile migraine, confirming previous findings in adult migraineurs. [11][12][13][14][15][16][17] These studies have suggested the hypothesis that higher VEP amplitude can be an expression of neuronal hyperexcitability of the visual pathway or of the cortex related to a lowered threshold for migraine attacks. 18 The abnormal information processing has been interpreted as an interictal cortical dysfunction originating in the brain stem, in particular by the serotoninergic pathway, leading to a low preactivation level of the sensory cortices.…”
mentioning
confidence: 99%
“…A similar method of trace comparison has been used earlier. 25,[28][29][30][31] For that reason, 23 ordinates, equally spaced distribution, they were transformed to Fisher's z-scores to satisfy the normality assumption and used in Student's paired and nonpaired tests to establish possible statistical differences between patients and normals All necessary computations were carried out by preparing programs for the Acorn's BBC microcomputer…”
Section: Methodsmentioning
confidence: 99%